2015
DOI: 10.1021/acs.langmuir.5b03603
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Monolayers of an Azobenzene Derivative on Silica and Their Interactions with Lysozyme

Abstract: The capability of the photoresponsive isomerization of azobenzene derivatives in self-assembled monolayer (SAM) surfaces to control protein adsorption behavior has very promising applications in antifouling materials and biotechnology. In this study, we performed an atomistic molecular dynamics (MD) simulation in combination with free-energy calculations to study the morphology of azobenzene-terminated SAMs (Azo-SAMs) grafted on a silica substrate and their interactions with lysozyme. Results show that the Azo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 61 publications
1
34
1
Order By: Relevance
“…In previous simulation studies, the protein must overcome the interfacial hydration layer and then adsorb onto different surfaces, such as polyethylene, , graphene, SAM, , etc., which is the so-called dehydration. Wei et al ,, demonstrated the significant role of the dehydration process on a hydrophobic surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous simulation studies, the protein must overcome the interfacial hydration layer and then adsorb onto different surfaces, such as polyethylene, , graphene, SAM, , etc., which is the so-called dehydration. Wei et al ,, demonstrated the significant role of the dehydration process on a hydrophobic surface.…”
Section: Resultsmentioning
confidence: 99%
“…In previous simulation studies, the protein must overcome the interfacial hydration layer and then adsorb onto different surfaces, such as polyethylene, , graphene, SAM, , etc., which is the so-called dehydration. Wei et al ,, demonstrated the significant role of the dehydration process on a hydrophobic surface. But for the highly hydrophilic surfaces like TiO 2 , the protein may only have a small number of residues that can be inserted into the internal water layer and have a certain strong interaction with the surface, causing weak adsorption, because it needs to overcome the large dehydration energy barrier.…”
Section: Resultsmentioning
confidence: 99%
“…Computer simulations, such as atomistic molecular dynamics (MD), have become a crucial approach to complement experimental studies and provide insight into the structural dynamics of the S protein and its interactions with ligands. Atomistic MD simulations compute trajectories and positions of N interacting atoms in a system by numerically solving Newton’s equations of motion. , Simulations can probe molecular structures with atomistic resolutions and sample MD from subnanoseconds to microseconds and elucidate molecular interactions. , …”
Section: Molecular Interactions Of Sars-cov-2 With the Ace2 Receptormentioning
confidence: 99%
“…Shing and co‐workers [ 248 ] conducted an atomistic molecular dynamics (MD) simulation to show that the ability of azobenzene‐terminated SAMs (Azo‐SAMs) grafted on a silica substrate to adsorb lysozyme was affected by the cis – trans configuration of the azo group. Calculations indicated that the lysozyme adsorbed on the high‐density trans ‐Azo‐SAM surface has a desorption free energy of about 60kT.…”
Section: Main Specific Applications Of Azobenzenementioning
confidence: 99%